Identifikasi Resiko pada Mesin Screw Press Menggunakan Metode Failure Mode and Effect Analysis (FMEA) pada CV.” Rezeki Bersama - Akmal, Abdiel Khaleil; Pamungkas, Iing; irawan, Heri tri (Jurnal Inotera, 2024)
CV. Rezeki Bersama is a producer of crude coconut oil (CCO) based in Alus-alus Village, Teupah Selatan District, Simeulue Regency, Aceh. CV. Rezeki Bersama employs 15 people at various production stations, including press machines. In practice, this research uses the Failure Mode and Effect Analysis (FMEA) method to determine the damage that occurred at the press station of the joint rezeki factory. The FMEA approach is used to assess the likelihood of failure in a manufacturing process, determining its severity, frequency of occurrence, and detectability. This study focuses on collecting machine damage data from January 3 to February 3 2024 and evaluating it to determine the Risk Priority Number (RPN) value which will be used to indicate the priority of repairs needed. This research aims to provide recommendations for repair and prevention of damage in the future, as well as increasing the reliability and efficiency of the company's operations.